Parental Separation and its Relation to Children’s Underachievement in Primary School Education - Odeh, Dr. Adnan; Omari, Nedaa Al- (IJRDO- Journal of Educational Research, 2017)
This study aims at investigating the relationship between parental separation (parental divorce) and the underachievement of children in the primary stage. The study sample consists of (100) children from two public schools (Mutah School for Girls and Al-Qurtubi School for Boys), the Institution of Legal Aid and the Family Protection Center. The average includes (50) children suffering from the problem of separation, and (50) live in stable families in Zarqa City in Jordan. The data is collected from several sources: First, the pupils’ marks during the preceding two years for all the sample members except the second-grade pupils whose marks of only one year are considered. Second, the data is collected in collaboration with home-room teachers, school records, and special records of the pupils who suffer from separation problems. Third, parents of the target sample group particularly the incubating father or mother after separation to know about their children’s educationl records. To answer the study questions, arithmetic means and standard deviations are used. The study results reveal that there are differences with statistical significance in achievement between boys and girls in favor of the girls. The study results also show that there are differences with statistical indications between stable family children and separated families in favor of the children of stable families, Furthermore, the results show that there is some linking relation between the pupils’ achievement and the secure and safe situation of the families where they live.